2012
DOI: 10.1073/pnas.1115485109
|View full text |Cite
|
Sign up to set email alerts
|

Peptide tag forming a rapid covalent bond to a protein, through engineering a bacterial adhesin

Abstract: Protein interactions with peptides generally have low thermodynamic and mechanical stability. Streptococcus pyogenes fibronectin-binding protein FbaB contains a domain with a spontaneous isopeptide bond between Lys and Asp. By splitting this domain and rational engineering of the fragments, we obtained a peptide (SpyTag) which formed an amide bond to its protein partner (SpyCatcher) in minutes. Reaction occurred in high yield simply upon mixing and amidst diverse conditions of pH, temperature, and buffer. SpyT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
1,581
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,331 publications
(1,603 citation statements)
references
References 52 publications
16
1,581
2
4
Order By: Relevance
“…The library members, detailed in Table 1, range in length from 7-59 amino acids and encode a wide variety of functions such as binding to various inorganic substrates (GBP, CNBP, QBP, MBD and AFP8), nucleation of mineral and metallic nanostructures (A3, CLP12, CT43 and Mms6), and a highly specific catalytic interaction with a protein (SpyTag) 15,[21][22][23][24][25][26][27][28][29][30][31] . Each peptide domain was cloned as C-terminal fusions to CsgA with an intervening six-amino-acid flexible linker (Table 1) and these plasmids were expressed in LSR10 cells to produce 12 different BIND biofilms.…”
Section: Csga Peptide Fusions Retain Amyloid Self-assembly Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The library members, detailed in Table 1, range in length from 7-59 amino acids and encode a wide variety of functions such as binding to various inorganic substrates (GBP, CNBP, QBP, MBD and AFP8), nucleation of mineral and metallic nanostructures (A3, CLP12, CT43 and Mms6), and a highly specific catalytic interaction with a protein (SpyTag) 15,[21][22][23][24][25][26][27][28][29][30][31] . Each peptide domain was cloned as C-terminal fusions to CsgA with an intervening six-amino-acid flexible linker (Table 1) and these plasmids were expressed in LSR10 cells to produce 12 different BIND biofilms.…”
Section: Csga Peptide Fusions Retain Amyloid Self-assembly Functionmentioning
confidence: 99%
“…5b-g). We recombinantly produced GFP-SpyCatcher and a non-functional mutant 28 (GFP-SpyCatcher E77Q ) and applied cell lysates containing these proteins to SpyTag-BIND or wild-type CsgA biofilms. Analysis by epifluorescence microscopy revealed, as expected, that only the combination of biofilms composed of CsgA-SpyTag incubated with GFP-SpyCatcher resulted in covalent attachment (Fig.…”
Section: Nature Communications | Doi: 101038/ncomms5945mentioning
confidence: 99%
“…The gelation rate of the current CarH C hydrogel system mainly depends on two events: the SpyTag-SpyCatcher reaction and AdoB 12 -dependent CarH C self-assembly. The SpyTag-SpyCatcher reaction is likely to be the rate-limiting step, because its secondorder rate constant is ∼1.4 × 10 3 M −1 s −1 , which is far from the diffusion limit and substantially slower than some other biomolecular interactions, such as the widely used streptavidin-biotin interaction (26). The reaction kinetics of SpyTag-SpyCatcher can be optimized through directed evolution to accelerate the gelation.…”
Section: Resultsmentioning
confidence: 99%
“…Genetically encoded SpyTag (A)-SpyCatcher (B) chemistry, inspired by an isopeptide bond-containing bacterial adhesin, consists of a peptide/protein pair that can spontaneously form an isopeptide bond on binding under mild physiological conditions (26). Because of its high efficiency and modularity, this chemistry has led to a number of applications, including control of biomacromolecular topology, synthesis of bioactive and "living" materials, and biomolecular imaging (16,18,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…CnaB2 domain locks itself together by forming a spontaneous isopeptide bond between Lys and Asp and this reaction is irreversible. Zakeri and colleagues earlier showed that CnaB2 domain could be split and engineered into two parts, a peptide (SpyTag) and a protein (SpyCatcher) and that these two could form amide bond irreversibly just by mixing the two components together (Zakeri et al, 2012). VLPs expressing SpyTag or Spy Catcher can thus be linked potentially to any antigen that is fused to either SpyCatcher or SpyTag respectively.…”
Section: Synthetic Vlpsmentioning
confidence: 99%